Implementasi Struktur Data Array dalam Sistem Perpustakaan Berbasis Web dengan Python Flask - Rudianto; Sapaatullah , Asep; Rakhim Setya Permana, Basuki; Darip, Mochammad (AMIK STIEKOM SUMATERA UTARA, 2025)
− Library services must provide convenience for users in finding books, journals, and other references, and over time, especially in the digital era, libraries must be able to adapt to the rapid evolution of information technology. Technological transformation is expected to improve the efficiency, speed, and quality of library services. However, many library services still rely on manual systems in managing book collections and circulation services. This manual system causes various problems, ranging from difficulty in finding information on book collections, inefficient recording, to long queues for the borrowing process. In addition, manual services are often unable to provide real-time book availability information, thereby reducing user satisfaction. Therefore, a technology-based solution is needed to improve the efficiency of library management and make it easier for users to access information. One approach that can be used is the development of a web-based library system using the Python Flask framework by utilizing array data structures to store book collection information in an organized manner. The results of the implementation of this system show how information technology, especially Python Flask and array data structures can be used to overcome library service problems in universities, such as integrating book management by admins, searching for books based on keywords, updating book availability status, updating borrowing status, and ordering online. This information is very useful for users to improve the efficiency of librarians' work in increasing satisfaction with library services, thus making library services more responsive to user needs.